Quantitative interpretation of discharges recorded in concrete dam foundations - Braga Farinha, M. L. (2011)
This paper presents a study focused on the viability of using simplified statistical methods of quantitative interpretation in the analysis and prediction of foundation behaviour. The shape of the curve which represents the influence that changes in reservoir level have on discharges in a concrete dam foundation was established using a hydromechanical numerical model. Discharges recorded in both single drains and seepage measuring weirs of two large Portuguese dams were analysed. The study carried out highlights the difficulties in interpreting recorded discharges, as they are not the sum of a series of structural responses which can be clearly identified. Conclusions are drawn regarding the accuracy of these methods when used in the analysis of the hydraulic behaviour.